Homo villicus in the cinema environment.: Justifiably and limits of the index. - Chmil, Hanna; Korablova, Nadiia; Bezruchko, Oleksandr; Zhukova, Nataliia (Convergences - Journal of Research and Arts Education, 2024)
The relevance of the topic of Homo villicus lies in its capacity to disrupt conventional paradigms of human representation and cultural understanding within the sphere of symbolism. The aim of this study is to investigate Homo villicus within the realm of symbolic representation, examining its unique characteristics and its role in contemporary philosophical discourse. The study employs a multidisciplinary approach, encompassing literature review, conceptual analysis, discourse analysis, case studies, content analysis, comparative analysis, psychological assessments, ethical considerations, and critical discourse analysis. The results of this study highlight the importance of an acratic approach to governance that uses Homo villicus, generating a counter-hegemonic discourse and intensifying the interaction between culture, cinema, and self-management. This study highlights the dynamic cultural influence of Homo villicus, which actively seeks to balance its inner forces and “build itself” through self-revolution. Furthermore, it explores the cinematic nature of self-construction, emphasizing the participation of viewers in the creation of screen products and the role of film in directly representing behavior. It also highlights the potential of Homo villicus in transforming dissatisfied models into personal models. Homo villicus’ distinctive self-demonstration technology, drawing from contemporary expositions and eschewing reliance on prior presentations, underscores its role as an innovative lens through which to explore cultural history on its terms.